The Photosensitising Clinical Agent Verteporfin Is an Inhibitor of SPAK and OSR1 Kinases. (22nd August 2018) - AlAmri, Mubarak A.; Kadri, Hachemi; Alderwick, Luke J.; Jeeves, Mark; Mehellou, Youcef
Abstract: STE20/SPS1‐related proline/alanine‐rich kinase (SPAK) and oxidative‐stress‐responsive kinase 1 (OSR1) are two serine/threonine protein kinases that play key roles in regulating ion homeostasis. Various SPAK and OSR1 mouse models exhibited reduced blood pressure. Herein, the discovery of verteporfin, a photosensitising agent used in photodynamic therapy, as a potent inhibitor of SPAK and OSR1 kinases is reported. It is shown that verteporfin binds the kinase domains of SPAK and OSR1 and inhibits their catalytic activity in an adenosine triphosphate (ATP)‐independent manner. In cells, verteporfin was able to suppress the phosphorylation of the ion co‐transporter NKCC1; a downstream physiological substrate of SPAK and OSR1 kinases. Kinase panel screening indicated that verteporfin inhibited a further eight protein kinases more potently than that of SPAK and OSR1. Although verteporfin has largely been studied as a modifier of the Hippo signalling pathway, this work indicates that the WNK‐SPAK/OSR1 signalling cascade is also a target of this clinical agent. This finding could explain the fluctuation in blood pressure noted in patients and animals treated with this drug. Abstract : Building barriers : Two examples of serine/threonine protein kinases control the function of a series of ion co‐transporters, and hence, cellular electrolyte balance. Animal models with impaired signalling of these kinases exhibit reduced blood pressure. Herein, we report identification and characterisation of verteporfin as a potent inhibitor of these kinases.